Stability of rice bran oil extracted by SFE and soxhlet methods during accelerated shelf-life storage - Mariod, Abdul Basit; Ismail, Maznah; Abd Rahman, N. F.; Matthaus, Bertrand (Consejo Superior de Investigaciones Cientificas, 2014)
Supercritical fluid high oryzanol (SFE HO) and supercritical fluid low oryzanol (SFE LO) rice bran oils were obtained and compared with that extracted by the Soxhlet (SOX) method. Their composition and stability during storage were determined. The amount of unsaponifiable matter and gamma oryzanol of SFE samples were significantly (p < 0.05) higher than SOX. While the amount of tocopherol in SOX (4.0 mg·g-1) was higher than that reported in SFE HO and SFE LO, at 3.2 and 2.6 mg·g-1, respectively. After storage for 42 days at 70 °C the PV, FFA%, conjugated diene and p-anisidine values of SOX were higher than those of SFE HO, and SFE LO. The SFE samples showed better stability than SOX under successive heating and the addition of BHA decreased PV, FFA%, conjugated diene and p-anisidine levels in all samples.